Strategi Pengelolaan Pendidikan pada Pesantren Modern di Wilayah Kabupaten Aceh Besar - Indra Kurniawan (Tadabbur: Jurnal Peradaban Islam, 2020)
There is no doubt that the educational process in modern Islamic boarding school is very orderly and organized, all of this is did’nt escape from the good management of the Islamic boarding school itself. Therefore, the author pleased to examine the Educational Process Management Strategy in Modern Islamic Boarding Schools in the Aceh Besar Region. The Islamic boarding school mean are: Al Falah Abu Lam U Islamic Boarding School, Al Manar and Oemar diyan Islamic Boarding School. The author used kualitatif method here, The datas comes from influential figures in the islmaic boarding school, Likes; The leader of the Modern Islamic boarding school, headmaster of school and one of his ustadz (inside teacher). The interesting thing in this research is that Modern Islamic Boarding Schools have been tested and are capable of creating Islamic cadres in the future in their own way. The way they do it is a deep management strategy, starting from program planning, implementation, evaluation and follow-up, that’s all carried out jointly with the teachers inside for the implementation of an educational process that runs well and regularly and to produce quality alumni.